Terrestrial Electrical Resistivity Tomography (ERT) profile surveys acquired in the Trunvel and Kerallé valleys, Brittany, North-West France - Aneta Gorczyńska; Pierre Stéphan; Ophélie David; Gillian Stephan; Bernard Le Gall; Yvan Pailler; Muriel Vidal (PANGAEA, 2025)
This dataset contains eight terrestrial Electrical Resistivity Tomography (ERT) profiles, collected between May 2017 and April 2018 in the Trunvel and Kerallé valleys, Brittany, North-West France. The measurements were acquired as part of the doctoral project "Paleogeographic changes and coastal archaeological remains in Brittany during the Middle and Late Holocene: Contributions of a multidisciplinary and multi-scaled approach, with the aim of reconstructing the Holocene evolution of small estuarine systems on the North-West French coast". The 2D subsurface profiles were obtained using a Terrameter LS 2 (ABEM) with an array of 64 electrodes and a Wenner array protocol. A computer inversion program (Res2Dinv), which incorporates topography and generates images of the resistivity distribution, was used. ERT profiles were conducted with an electrode spacing ranging from 1 m to 2 m. Each electrode was precisely leveled using a TopCon HyperV Differential GPS, and local French ordnance datum (Nivellement Général de la France) geodetic benchmarks were used as references. The objective of this study was to identify the depth and geometry of Holocene sedimentary deposits. This dataset contains raw data, inversion results, and the geographical coordinates of each electrode.